MicroRNA-587 Functions as a Tumor Suppressor in Hepatocellular Carcinoma by Targeting Ribosomal Protein SA. (7th September 2020) - Chen, Miao; Wang, Duo; Liu, Junjie; Zhou, Zhizhan; Ding, Zhanling; Liu, Lianfeng; Su, Danke; Li, Hang
Abstract : Background . Hepatocellular carcinoma (HCC) is one of the most highly aggressive cancer worldwide with an extremely poor prognosis. Evidence has revealed that microRNA-587 ( miR-587 ) is abnormally expressed in a series of cancers. However, its expressions and functions in HCC have not been clearly acknowledged. Methods . We detected the expression level of miR-587 both in the Gene Expression Omnibus (GEO) database and 86 paired clinical HCC tissues together with paired adjacent normal tissues by quantitative real-time PCR (qRT-PCR). Afterwards, the transfected HCC cell line SMMC-7721 cells were collected for the cell proliferation assay, cell-cycle arrest, cell migration, and invasion assays to explore the roles of miR-587 in regulating cellular function. In addition, bioinformatics analysis, combined with qRT-PCR and dual-luciferase reporter assays, were performed to confirm whether ribosomal protein SA ( RPSA ) mRNA was the direct target gene of miR-587 . Moreover, the Cancer Genome Atlas (TCGA) and GEO databases as well as 86 paired clinical HCC tissues were used to verify the negative regulation between miR-587 and RPSA . Results . In the present study, both the GEO database (GSE36915 and GSE74618) analysis and qRT-PCR analysis of 86 paired clinical tissues showed that miR-587 was significantly downregulated in HCC tissues. The overexpression of miR-587 inhibited proliferation, cell cycle, migration, and invasion in SMMC-7721 cells. In addition, miR-587 directly interacted with the 3 ′ -untranslated region (UTR) of RPSA . Moreover, miR-587 overexpression directly suppressed RPSA expression, and the two genes were inversely expressed in HCC based on the analyses in TCGA and GEO (GSE36376) databases and qPCR analysis of 86 paired clinical tissues. Conclusion . Our results demonstrate that miR-587 is downexpressed in HCC and regulates the cellular function by targeting RPSA .